Pengaruh Model Childrean Learning in Science (CLIS) Terhadap Kemampuan Berfikir Kritis Siswa di UPT SDN 207 Gresik - Sa'diyah; Ria Resti Fauziah (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2024)
This research aims to find out: Is there an influence of ability Critical Thinking Students taught using the Children Learning in Science (CLIS) model in learning science and science on the topic of magnetic force. Critical thinking is to include judgment or careful evaluation, such as assessing the suitability of an idea or product. Muhibbin identifying rational thinking and critical thinking are manifestations learning behavior, especially those related to solutions to these problems. Matter It is understood that students have critical thinking skills use basic principles and foundations of understanding to answer questions, such as